DESIGN OF RECTANGULAR WITH 3 SLOT MICROSTRIP ANTENNA FOR APPLICATION LTE 2.1 GHz - Yusnita Rahayu; Irfan Alwandi Pohan (Universitas Mercu Buana, 2018)
A rapid development of telecommunications technology, and over time, the existing network technologies continue to be developed. To create the latest technology called Long Term Evolution (LTE). With the technology that has a high transmission speed, of course, required new devices that can operate on this network. Antennas are needed on these networks is an antenna that is small and easily integrated. In this case, the right antenna to be used is the microstrip antenna. In this paper, which will be designed antenna is an antenna feed line rectangle shapes that can operate at a frequency of 2.1 GHz.